Effect of stroboscopic visual training in athletes: a systematic review - Jothi, S; Dhakshinamoorthy, J; Kothandaraman, K. (Journal of Human Sport & Exercise, 2025)
Background : Visual abilities and motor performance are the key factor in athletes to improve their performance. One emerging technology to enhance athletes' visuomotor and cognitive abilities is SVT. This paper aims to show how SVT can be used as an intervention technique in athletics to enhance athletes' performance. Any research that examined the use of strobe glasses as a training aid for physically fit athletes was taken into consideration for this evaluation.